2007
DOI: 10.2174/138945007780618535
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Transporter 1 Inhibitors and Modulation of NMDA Receptor-Mediated Excitatory Neurotransmission

Abstract: In the central nervous system, glutamate is essential for a proper synaptic communication in neuronal networks supporting critical behavioral activities such as learning and memory. Dysfunction of glutamatergic excitatory neurotransmission has been implicated in numerous neurological and pyschiatric disorders and a growing body of research suggests that potentiation of NMDA receptor function may represent a novel approach for the treatment of schizophrenia. An actively pursued strategy to potentiate NMDA recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Alternatively, B 0 AT3 might function to remove a neurochemically active substrate from the synapse. For example, proline and glycine, both likely substrates for B 0 AT3, have been shown to modulate glutamatergic signaling (30,31). It is interesting to note that PROT, B 0 AT2, B 0 AT3, and the brain-specific isoform of the imino transporter are all expressed with relative specificity in the brain and all transport proline with apparent affinities in the submillimolar range.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, B 0 AT3 might function to remove a neurochemically active substrate from the synapse. For example, proline and glycine, both likely substrates for B 0 AT3, have been shown to modulate glutamatergic signaling (30,31). It is interesting to note that PROT, B 0 AT2, B 0 AT3, and the brain-specific isoform of the imino transporter are all expressed with relative specificity in the brain and all transport proline with apparent affinities in the submillimolar range.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments suggested that this down-regulation might be associated with the trafficking of the transporter, although the molecular mechanisms behind this process remained unexplored. Because GLYT1 is a major regulator of the concentration of glycine both at inhibitory and excitatory synapses, it represents a target for potentially important drugs with antipsychotic and analgesic properties (6). Thus, we have further investigated the mechanisms involved in the endocytic trafficking of this transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mice lacking GLYT1 have impaired glycinergic neurotransmission, which has been attributed to an increase in extracellular glycine close to the strychnine-sensitive glycine receptor (4). Moreover, GLYT1 has been identified in neuronal elements closely associated with the glutamatergic pathways throughout the brain (5,6). GLYT1 is enriched in presynaptic buttons, where it largely co-localizes with the vesicular glutamate transporter vGLUT1.…”
mentioning
confidence: 99%
“…The more advanced target is the inhibition of glycine reuptake by GlyT1 in the perisynaptic region (Javitt, 2008(Javitt, , 2009. Preclinical studies indicate GlyT1 inhibitors augment NMDA receptor-dependent processes in vitro and in vivo (Sur and Kinney, 2007;Bridges et al, 2008;Yang and Svensson, 2008). Clinical proof of concept has been obtained with sarcosine, a naturally occurring intermediate in glycine metabolism that is a low-affinity GlyT1 inhibitor (Zhang et al, 2009a,b).…”
Section: F N-methyl-d-aspartate Receptor Potentiationmentioning
confidence: 99%